Tantangan Dalam Manajemen Insiden Lingkungan Di Destinasi Wisata Lautan Tropis: Studi Kasus Kapal Pesiar Caledonian Sky - Reski Amalia; Agussalim Burhanuddin (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Tropical ocean tourism destinations are very common in Indonesian waters and are one of the main attractions for foreign tourists from abroad, especially for tourists who are looking for exclusive experiences such as cruise ship travel. This can certainly provide economic benefits to the Indonesian tourism industry and support the economy of the local community. However, it cannot be denied that the high volume of tourists in a tourist destination can affect the sustainability of the marine environment in the future. Through this research, the author will discuss the challenges of environmental incident management for tropical marine tourism destinations, with a focus on the incident of the Caledonian Sky Cruise Ship's collision with coral reefs. In this research, the author will focus on the obstacles and challenges that exist in the process of resolving the Caledonian Sky Cruise Ship case which is reviewed in various aspects, namely international and national law. By combining the methods of policy analysis, case studies, and library research, the author will identify aspects related to the Caledonian Sky Cruise Ship incident. In this research the author will discuss the Indonesian government's efforts in resolving the case and the various challenges that exist in the process of resolving the Caledonian Sky Cruise Ship incident